KEGIATAN MONITORING TERSTRUKTUR UNTUK MENINGKATKAN KOMPETENSI DAN KINERJA GURU DALAM KEGIATAN BELAJAR MENGAJAR DI UPTD SDN BANCARAN 4 KECAMATAN BANGKALAN KABUPATEN BANGKALAN TAHUN 2019/2020 - Atik Zaenab; Kacung Wahyudi (re-JIEM (Research Journal of Islamic Education Management), 2019)
The results of the study indicate that: a. the quality of the assignment teacher preparation program at the Mambaul Ulum Islamic Boarding School in Panaan Palengaan Pamekasan, namely 1) The curriculum that is used combines the pesantren curriculum, pesantren programs, and activities and the Madrasah Aliyah curriculum in general, 2) The existence of Islamic boarding school support for the applied curriculum, 3) The creation of a single teaching staff so that the term M2 co-ordinates prospective teacher assignments, 4) The existence of regional programs or blocks, 5) Suitability of the background of the teaching staff with their education, 6) Form of quality improvement resulting from the application of existing curriculum, development what has been done, and ask for input from the teacher who has carried out their duties. b Constraints of Mambaul Ulum Islamic Boarding Schools in Panaan Palengaan Pamekasan in implementing teacher preparation tasks, namely, 1) Less skilled and creative teaching staff in presenting interesting programs, thereby reducing students' interest and motivation in participating in the program, 2) The lack of interest of santri to learning causes the pesantren programs to run less optimally, 3) The lack of facilities and finance makes the programs implemented less varied.